Integrated design, modelling and analysis of two-wheeled wheelchair for disabled - Aula, Abqori; Altalmas, Tareq M.; Ahmad, Salmiah; Akmeliawati, Rini; Sidek, Shahrul Na'im (2013)
Two-wheeled wheelchairs are considered as high nonlinear and complex system. This complex system as well as the need for this system to help disabled people has motivated researchers around the world to do their work in this area. But the recent designs have some limitations. This paper will come with new design to come over these limitations. A new design of two-wheeled wheelchair has been proposed with physical and mathematical models. The system was tested by Linear-quadratic regulator LQR and the result showed that the linear model is working well.